Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $M$ be a module over Noetherian ring $R$ such that $\operatorname{H}^1_I(M)=0$ for every ideal $I$ of $R$. Show that $\operatorname{H}^1_J(\Gamma_I(M))=0$ for every ideal $J$.

I tried to prove it by Mayer-Vietoris sequence but I can't, unfortunately. Also applied the following sequences $$0‎\rightarrow \Gamma_I(M)‎\rightarrow M‎\rightarrow D_I(M)‎\rightarrow 0 $$ $$0‎\rightarrow \Gamma_I(M)‎\rightarrow M ‎\rightarrow M/\Gamma_I(M)‎\rightarrow0 .$$ Moreover, since $\operatorname{H}^1_I(M)=0$ for every ideal $I$ of $R$ then Proposition 4.1.3 from Brodmann-Sharp, Local Cohomology, suggests that $\operatorname{H}^i_I(M)=0$ for all $i\geq 0$.

Background: $D_I(M)$ means ideal transform with respect to $I$ and the first exact sequence obtains from Theorem 2.2.4(i)(c) in the same book.

share|cite|improve this question
Thanks.Finally, I could prove it. – Angel Jan 5 '13 at 8:58
up vote 1 down vote accepted

Sketch of proof:

Let $J=(x_1,\dots,x_n)$. If $J\subseteq I$ it's done. Let $J‎\nsubseteq‎ I$ therefore $\exists x\in J-I $. By 4.1.22 from the same book we have the following exact sequence $$0‎\rightarrow‎ \Gamma_{I+x}(M)‎\rightarrow‎\Gamma_I(M)‎\rightarrow‎ \Gamma_I(M_x)‎\rightarrow‎ 0=H^1_{I+x}(M).$$ Applying $\Gamma_J(-)$ we get $$ \cdots‎\rightarrow‎ \Gamma_J(\Gamma_I(M_x))‎\rightarrow‎ H^1_J(\Gamma_{I+x}(M))‎\rightarrow‎ H^1_J(\Gamma_I(M))‎\rightarrow‎ H^1_J(\Gamma_I(M_x))‎\rightarrow‎\cdots $$ Now use the independence Theorem $$\Gamma_J(\Gamma_I(M_x))\cong \Gamma_J(\Gamma_{I_x}(M_x))\cong \Gamma_J(\Gamma_I{(M )})_x\cong \Gamma_{J_x}(\Gamma_I(M))_x=0. ~ (Since~ x\in J)$$ $$H^1_J(\Gamma_I(M_x))\cong H^1_J(\Gamma_{I_x}(M_x))\cong H^1_J(\Gamma_I{(M )})_x\cong H^1_{J_x}(\Gamma_I(M))_x=0.~ (Since~ x\in J)$$ Therefore $H^1_J(\Gamma_{I+x}(M))‎\cong‎ H^1_J(\Gamma_I(M))$. Continuing as before we have $$H^1_J(\Gamma_I(M))\cong H^1_J(\Gamma_{I+J}(M))‎=0. ~(Since~ J\subseteq I+J)$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.